Biogeophysical Method for Searching and Exploration of Oil Fields - M.Sh. Mardanov; R.G. Khannanov; V.B. Podavalov; U.R. Galimov; V.N. D’yachkov (Учёные записки Казанского университета: Серия Естественные науки)
The problems of using biogeophysical method (BGPh method) to reveal and map oil accumulations in sedimentary rocks are considered. A working hypothesis of BGPh anomaly generated due to the electromagnetic nature (background) of the observed phenomenon has been posited. Methodology for fieldworks and interpretation of the obtained materials has been developed. It is successfully applied in more than 30 objects of the oil companies under study. The results of deep-hole drilling demonstrate in a convincing way that BGPh method provides highly accurate predictions. BGPh studies of old oil fields make it possible to detect zones with commercial reserves of oil, where water cutting of the well pro-duction does not exceed 75–80%. Therefore, there are prospects for areal monitoring of the developed field in order to reveal “washed-out” zones, as well as areas unaffected by exploitation and lithologically isolated (“bypassed” oil).